A differentiated approach to complex treatment of radioiodine-induced salivary gland lesions - Kopchak, A. V.; Makarenko V. А. (Modern medical technology, 2023)
The number of patients treated with radioactive iodine for highly differentiated thyroid carcinomas who develop chronic radiation-induced salivary gland lesions is constantly rising, that necessitates the search for new pathogenetically focused approaches and methods of treatment considering the stage of the process and pre-existing risk factors. Aim. The aim of the study was to determine the clinical effectiveness of a new pathogenetic therapy based on a differentiated and personalized approach compared to standard approaches for radioactive iodine-induced salivary glands lesions. Materials and methods. The prospective study included 60 patients (5 men and 55 women, aged 45.0 ± 0.5 years) with chronic radioactive iodine-induced salivary gland lesions following radiation treatment. The patients were divided into 2 groups depending on the type of therapy they received. The clinical effectiveness of the developed methods was evaluated with the use of objective clinical criteria within a year after radioiodine therapy. Results. Our approach demonstrated reliably improved treatment outcomes compared to standard techniques. Thus, the treatment we offered, which included long-acting glucocorticoids, proteolysis inhibitors, and sialendoscopic techniques, completely resolved or minimized the clinical manifestations of the disease in 73.3 % of patients (33.3 % in the control group) one year after the start of treatment. The therapeutic effect was not found only in 6.7 % of patients compared to 20.0 % in the control group. The developed approach effectively eliminated saliva outflow disorders and inflammatory symptoms, with significantly better results of the treatment group compared to the control group (χ2 = 6.20; p < 0.05 and χ2 = 6.67; p < 0.05). The disorders of secretory function were more difficult to correct, especially in the later stages of the disease, associated with severe xerostomia development. Conclusions. The differentiated use of the developed pathogenetically oriented complex treatment enabled us to significantly improve the condition of patients with chronic radiation-induced sialoadenitis during the observation period of up to 1 year. This treatment also outperformed traditional symptomatic correction in solving the problem of saliva retention (χ2 = 6.67; p < 0.05) and inflammation manifestations (χ2 = 6.20; p < 0.05). Clinical symptoms of the disease were fully resolved or reduced in 73.3 % of patients versus 33.3 % in control group and partially improved in 20.0 % versus 46.0 % of control group within 12 months after radiation exposure. Longterm treatment and strict adherence to lifestyle and oral hygiene recommendations were required to achieve the desired clinical result and stable remission of clinical symptoms in patients with chronic radiation sialoadenitis.